Survey of Student Interest in Physical Education Learning in Relation to the Availability of Facilities and Infrastructure at SMP Negeri 1 Surakarta - Puput Devi Safitri; Gatot Jariono; Nurhidayat Nurhidayat (Center for Sports Science , Faculty of Sport Science, Universitas Negeri Padang, 2026)
This study aims tox analyze the factors influencing students’ learning motivation in Physical Education, Sports, and Health (PESH / Pendidikan Jasmani, Olahraga, and Kesehatan – PJOK) at SMP Negeri 1 Surakarta. The examined factors include internal student factors, external factors in the form of teacher and peer support, and the availability of sports facilities and infrastructure. This study employed a descriptive quantitative approach with a survey design. The sample consisted of 89 students selected using simple random sampling from a total population of 958 students. Data were collected using a Likert-scale questionnaire and analyzed using descriptive percentage statistics. The results indicate that students’ learning motivation is classified in the high category, with an average score of 77.36%. Internal factors contributed 78.51%, external factors 79.13%, and facilities and infrastructure 74.46%. These findings demonstrate that teacher and peer support are the dominant factors influencing students’ learning motivation in PESH, despite limitations in sports facilities and infrastructure. This study highlights the importance of strengthening social support and instructional quality to sustain students’ learning motivation in Physical Education